A case study on the implementation of the conceive – design – implement – operate framework. Issue 1 (January 2017) - Namasivayam, Satesh; Fouladi, Mohammad Hosseini; Chong, Chien Hwa
The conceive – design – implement – operate educational framework is implemented by educators to generate graduates who are able to tackle complex engineering challenges. A set of 12 standards define this framework and how to implement it. Taylor's School of Engineering has been part of this framework for the past six years and utilises it in the design of its engineering curriculum. This paper shares the Taylor's experience in adopting the framework by explaining the aforementioned underlying standards. The article guides the reader to evaluate the compliance to each standard, and the corresponding success in implementation.